2013
DOI: 10.1155/2013/572134
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Outcome Measures for Exercise Intervention in People with Parkinson’s Disease

Abstract: Background. It is widely believed that exercise improves mobility in people with Parkinson's disease (PD). However, it is difficult to determine whether a specific type of exercise is the most effective. The purpose of this study was to determine which outcome measures were sensitive to exercise intervention and to explore the effects of two different exercise programs for improving mobility in patients with PD. Methods. Participants were randomized into either the Agility Boot Camp (ABC) or treadmill training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 30 publications
8
46
0
1
Order By: Relevance
“…They concluded that changes in the velocity of movements at a single joint are not a good reflection of the overall clinical state of patients with PD. King et al (2013) were interested in which outcome measures are sensitive to exercise intervention and explored the effects of two different exercise programmes for improving mobility in patients with PD. Thirty-nine participants were randomized into either the Agility Boot Camp (ABC) or treadmill training; 4x/week for 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that changes in the velocity of movements at a single joint are not a good reflection of the overall clinical state of patients with PD. King et al (2013) were interested in which outcome measures are sensitive to exercise intervention and explored the effects of two different exercise programmes for improving mobility in patients with PD. Thirty-nine participants were randomized into either the Agility Boot Camp (ABC) or treadmill training; 4x/week for 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies almost always compare an intervention protocol with a placebo intervention or no intervention at all (29). Due to ethical considerations and the fact it is a progressive neurodegenerative disease, we opted not to establish a control group since the assignment of patients to this group would harm their clinical progress, considering that the benefits of physical therapy for PD patients are well-established in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…A Norwegian translation is in progress (Master's thesis, University of Oslo, 2015). The Mini-BESTest has been found to have good concurrent validity [5,8,9], and has satisfactory predictive validity in identifying future recurrent fallers in patients with PD, especially during the first 6 months following assessment [10].…”
Section: Introductionmentioning
confidence: 99%